Keterkaitan Citra Merek, Harga dan Kualitas Produk Terhadap Keputusan Pembelian Tinjauan Sistematis Literature Review - Sander, Dapit Alex; Chan, Arianis; Muhyi, Herwan Abdul (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2021)
Much research on purchasing decisions refers to price, product quality and brand image. This study aims to complement previous research. Research that has explored the relationship of brand image, price and product quality to purchasing decisions. The purpose of this study was to determine the operationalization of the influence of brand image, price, and product quality. This study will describe the interrelationships between variables in purchasing decisions in the context of marketing science. This study uses a systematic review process, namely an in-depth literature review of the results of 23 articles based on certain keywords and limitations. Based on the review produced a model that describes the influence of brand image, price and product quality on purchasing decisions. It is expected to be a reference and adoption of an approach to marketing activities. Future research is suggested to have more than one database and use more sources of research articles published over 10-20 years. It is hoped that future research with broad observations and results on how science continues to develop.